Decoding Digital Dilemmas: The Indonesian Journey From Facebook-Commerce Anxiety To Engaged Participation (Theoretical paper) - Ahmad Fauzi; Endang Siti Astuti fauzi; Edy Yulianto; Muhammad Iqbal (Cita Konsultindo Research Center, 2024)
Decoding Digital Dilemmas: The Indonesian Journey from Facebook-Commerce Anxiety to Engaged Participation delves into Indonesia's unique trajectory in the digital marketplace landscape, primarily focusing on Facebook as a platform for commerce. This paper uncovers the initial trepidation and uncertainties experienced by local merchants and consumers, attributed largely to unfamiliarity with the digital ecosystem and concerns about security, trustworthiness, and cultural fit. Drawing upon a mix of qualitative and quantitative data, we trace how these anxieties have evolved over time. A convergence of improved technological infrastructure, community-led knowledge sharing, and Facebook's localized strategies has led to an environment where digital commerce now thrives. The Indonesian case exemplifies how societies can transition from hesitation to active engagement in digital platforms, offering insights for other emerging markets navigating their own digital transformations.